Superconductivity in an infinite-layer nickelate superlattice - Wen Xiao; Zhan Yang; Shilin Hu; Yuzhou He; Xiaofei Gao; Junhua Liu; Zhixiong Deng; Yuhao Hong; Long Wei; Lei Wang; Ziyue Shen; Tianyang Wang; et al. (Nature Communications)
Abstract Recent observations of superconductivity in infinite-layer nickelates offer insights into high-temperature superconductivity mechanisms. However, defects and dislocations in doped films complicate the realization of superconductivity, limiting current research to superconducting nickelate heterostructures. The lack of research on superconductivity in superlattices composed of ultrathin nickelates severely impedes not only the exploration of the interface effect on superconductivity, but also the utilization of heterostructure engineering for exploring higher superconducting temperature T c. Here, we demonstrated superconducting infinite-layer nickelate superlattices [(Nd0.8Sr0.2NiO2)8/(SrTiO3)2]10 via topotactic reduction. Our study uncovered that only above a critical thickness can high-quality superlattices be achieved, with structural formation dependent on nickelate layer thickness. The superconducting superlattice showed a T c of 12.5 K and a 2D superconducting feature, indirectly indicate the intrinsic superconductivity of infinite-layer nickelates. Our study offers promising avenues for delving into the superconducting mechanism and for exploring multilevel interface engineering of infinite-layer nickelates, thus opening new horizons for the study of infinite-layer nickelates.